Clinical image-based procedures. from planning to intervention : International Workshop, CLIP 2012, Held in Conjunction with MICCAI 2012, Nice, France, October 5, 2012, Revised Selected Papers - Drechsler, Klaus (Lecture Notes in Computer Science, 2013)
This book constitutes the thoroughly refereed post-workshop proceedings of the International Workshop on Clinical Image-based Procedures: From Planning to Intervention, CLIP 2012, held in Nice, France, in conjunction with the 15th International Conference on Medical Image Computing and Computer-Assisted Intervention, MICCAI 2012. This successful workshop was a productive and exciting forum for the discussion and dissemination of clinically tested, state-of-the-art methods for image-based planning, monitoring and evaluation of medical procedures. The 16 papers presented in this volume were carefully reviewed and selected from 24 submissions.